Assessment of Interventions in Primary Health Care for Improved Maternal, New-born and Child Health in Sub-Saharan Africa: A Systematic Review. (October 2022) - Okonofua, Friday E.; Ntoimo, Lorretta F. C.; Adejumo, Oluwadamilola A.; Imongan, Wilson; Ogu, Rosemary N.; Anjorin, Seun O.
Primary health care (PHC) holds great potentials to improve maternal, newborn, and child health (MNCH) outcomes. However, there has been limited documentation of its effects on increasing universal access to maternal, newborn, and child health services in sub-Saharan Africa. Also, not adequately known are the most effective interventions to improve the delivery of PHC services in the region. The objective of this study was to conduct a systematic review of empirical evidence of interventions that improved access and quality of PHC services for maternal, newborn, and child health in sub-Saharan Africa. The protocol was registered on Prospero (Registration number CRD42019126029). Using terms related to primary health care and MNCH, we searched African Journals Online (AJOL), PubMed/Medline, Popline, ScienceDirect, Google Scholar, WHO Repository (IRIS), Directory of Open Access Journals (DOAJ), Cochrane Library, and reference lists for studies published in English between 2000 and 2019. Studies were included in the search if they reported interventions, and strategies implemented to improve quality and access to primary health care for maternal, newborn, and child health in sub-Saharan Africa. A total of 25 studies were included in the review. Effective interventions included financial incentives, task-shifting, community-directed engagements, training of providers, mobile health, cost-sharing, and supportive supervision among others. The result of this review contributes useful insight to guide the reformation, and development of new policies and programs for improving access and quality of primary health care delivery in sub-Saharan Africa, particularly to improve maternal and child health in the region. However, strategies to scale and sustain the successes need to be in place.